Improving the Quality of Instructor Services at BBPPMPV Business and Tourism through Visionary Leadership, Organizational Culture, and Achievement Motivation (A Quantitative Study Using Path Analysis and SITOREM) - Zulfikar,; Setyaningsih, Sri; Suhendra, (Technium Social Sciences Journal, 2025)
This paper investigates how organizational culture and visionary leadership influence the quality of instructor services in BBPPMPV Business and Tourism using achievement motivation as a mediator. Using a quantitative approach comprising path analysis and SITOREM, data were collected from 153 vocational high school teachers in DKI Jakarta who were graduates of the training.developing capacity Also I revised BBPPMPV Business and Tourism 2020–2024. The results revealed that visionary leadership (β = 0.217) and organizational culture (β = 0.193) have a significant direct impact on instructor service quality. In addition, both variables also affect instructor service quality indirectly through achievement motivation, which itself has a significant direct effect (β = 0.137) on instructor service quality. This study offers evidence-based governance at BBPPMPV Business and Tourism, a behavioral model. This study provides a strategic framework for institutional development, especially affecting initiatives for teacher performance improvement, by pointing out the achievement motivation mechanism linking visionary leadership and organizational culture to service outcomes.